Emerging Potential of Naturally Occurring Autophagy Modulators Against Neurodegeneration - Rahman, Md. Ataur; Rahman, Md Rezanur; Zaman, Toyfiquz; Uddin, Md. Sahab; Islam, Rokibul; Abdel-Daim, Mohamed M.; Rhim, Hyewhon (Bentham Science Publishers, 2020)
Background: Naturally-occurring products derived from living organisms have been shown to modulate various pharmacological and biological activities. Natural products protect against various diseases, which could be used for therapeutic assistance. Autophagy, a lysosome-mediated self-digestion pathway, has been implicated in a range of pathophyaiological conditions and has recently gained attention for its role in several neurodegenerative diseases. Methods: fn this current review, we emphasized the recent progress made in our understanding of the molecular mechanism of autophagy in different cellular and mouse models using naturally-occurring autophagy modulators for the management of several neuroclegenerative diseases. Resul&c: Accumulating evidence has- revealed that a wide variety of natural compounds such as alkaloids, polyphenols, terpenoids. xanthonoids, flavonoids, lignans, disaccharides. glycolipoproteins, and saponins are involved in the modulation of the autophagy signaling pathway. These natural products have been used to treat various neurodegenerative diseases such as Alzheimer's disease. Parkinson's disease. Huntington's disease, Amyotrophic lateral sclerosis, spinocerebellar ataxia, neuroblastoma, and glioblastoma. Although a number of synthetic autophagy regulators have been recognized as encouraging neurodegenerative therapeutic candidates, natural autophagy-regulating compounds have been of further interest as potential disease therapeutics, as they cause insignificant side effects. Conclusion: Existing in vitro and in vivo data are promising and highlight that naturally-occurring autophagyregulating compounds play an important role in the prevention and treatment of neurodegenerative disorders.